Peran Satpol PP dalam Penegakan Tentang Penanggulangan Prostitusi dan Perbuatan Asusila di Kabupaten Sukoharjo - Sitohang, Dahlan; Narpadie, Richard Jhan (PT. PENERBIT TIGA MUTIARA, 2024)
This research aims to determine the role and obstacles faced by the Govermental (Satpol PP) in enforcing regional regulations regarding the prevention of prostitution and immoral acts in Sukoharjo Regency. Research Subject Govermental (Satpol PP). The object of research in this study is the role of the Govermental in enforcing regional regulations regarding the prevention of prostitution and immoral acts. This type of research is qualitative research. The method used by researchers in this research is the descriptive method. The data collection technique uses 3 techniques, namely (1) observation, (2) interviews, and (3) presentation of documentation. The research results show that the position of the Govermental as a regional apparatus as its main task is basically aimed at assisting regional heads in enforcing regional regulations. Efforts to deal with perpetrators of prostitution and immoral acts in Sukoharjo Regency include judicial and non-judicial actions as well as closing localization places or places where the perpetrators follow up on every complaint that comes in which is reported by the public with early detection or searching for information related to prostitution and immoral acts. The obstacles faced by the Govermental in dealing with prostitution and immoral acts include the number of personnel capacity, perpetrators browsing through online media such as dating applications, limited quality of investigators and lack of facilities and infrastructure, low public awareness in enforcing order and peace and the lack of maximum technical regulations governing the problems faced.